Bioaccumulation of chemicals in fish : investigation of the dependence of depuration rate constant on lipid content of fish /: investigation of the dependence of depuration rate constant on lipid content of fish. ([2014]) - Brooke, David, 1957-; Crookes, M. J (Michael Jonathan), 1964-
No abstract available